Hatha Yoga vs Prenatal gymnastic: The Perfect Choice to Reduce Stress and Improve Health for Primigravid - Fernandez, Veronica; Lesmana, Ronny; Krisnadi, Sofie Riyani; Susiarno, Hadi; Tarawan, Vita Murniati; Iskandar, Shelly (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2025)
Abstract: Pregnancy is a critical period involving significant physiological and psychological changes, particularly in primigravida women who are more susceptible to anxiety and stress. Elevated stress levels during pregnancy may increase the risk of complications like high blood pressure, preeclampsia, and premature delivery. Non-pharmacological interventions like Hatha Yoga and gymnastic prenatalhave been widely recommended to improve maternal well-being. The purpose of this research was to evaluate and compare the impacts of two different interventions on maternal psychological and physiological health through a Systematic Literature Review (SLR) conducted in accordance with PRISMA guidelines. Relevant literature was retrieved from databases including Pubmed, Scopus, ScinceDirect, Google Scholar, focusing on research published between 2014 and 2024. The findings indicate that Hatha Yoga is more effective in reducing anxiety, cortisol levels, and systolic blood pressure, while prenatal gymnastic better supported diastolic blood pressure regulation and physical endurance for labor. Both interventions contribute to better cardiovascular function, increased oxygen saturation, and a smoother labor process. Additionally, yoga is associated with improved neonatal outcomes, while studies on prenatal exercise’s effects on newborn health remain limited. Future research should explore the long-term effects and key differences between these interventions to determine the most effective approach for maternal and neonatal health. These findings support integrating yoga and gymnastic prenatalinto antenatal care programs to enhance pregnancy outcomes.